The Comparison Between Students Career Beliefs in E-Game and Traditional Game Community Member - Alfan, Robbani (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2020)
This article contains the results of an analytical study about the comparison between Universitas Negeri Jakarta students career beliefs in e-game and traditional game community member. This study uses a descriptive survey method of cross-sectional study type, with the Career Beliefs Questionnaire adapted to Nancy E Betz's (1996) work. The study is carried out through 8 steps, namely (1) determining the object of study, (2) identifying the hypothesis, (3) identifying the population and sample, (4) determining the type of survey, (5) selecting the instrument, (6) administering the instrument, (7) data processing and analysis, and (8) article writing. The main finding of this article is that there are no significant differences in career beliefs between students who are members of the e-game and traditional game community. This study is useful as an empirical basis for the implementation of career counseling in higher education